Introduction of Setaria Grass and Gliricidia Legume as Feed in Relation to Increase of Ruminant Animal Productivity at Serang River Basin - Widiyanto (Widiyanto); E. Pangestu; V. D. Yunianto; Surahmanto (Surahmanto); T. B. Iskandar Moeda; Srimawati (Srimawati) (Buletin Peternakan, 1995)
Abstract dalam bentuk hard copy